2017
DOI: 10.2147/copd.s133854
|View full text |Cite
|
Sign up to set email alerts
|

A novel scoring index by Doppler echocardiography for predicting severe pulmonary hypertension due to chronic lung diseases: a cross-sectional diagnostic accuracy study

Abstract: BackgroundSevere pulmonary hypertension (PH) resulting from a chronic lung disease (CLD) (severe CLD-PH) requires more aggressive treatment due to its increased mortality compared with mild PH. Therefore, we developed a Doppler echocardiography scoring index (ESI) to predict severe CLD-PH.MethodsA derivation cohort of 107 patients with CLD who underwent echocardiography was classified into two groups, the normal/mild PH group and the severe PH group, based on the right heart catheterization. Meanwhile, we desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Progressively activated platelets with pseudopodia formation have heterogeneous sizes and may increase PDW accordingly. 16,17 The association of PDW with survival may be hypothetically linked with hypercoagulation, which plays a significant role in conditions associated with survival in COPD 18 and acute myocardial infarction. 19,20 Previously, PDW was found to increase in tumors (cervical and hepatocellular carcinoma, 21,22 breast and gastric cancer 23,24 ) and inflammatory disorders (sepsis 25 and acute pancreatitis 26 ) and was identified as a predictor for survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progressively activated platelets with pseudopodia formation have heterogeneous sizes and may increase PDW accordingly. 16,17 The association of PDW with survival may be hypothetically linked with hypercoagulation, which plays a significant role in conditions associated with survival in COPD 18 and acute myocardial infarction. 19,20 Previously, PDW was found to increase in tumors (cervical and hepatocellular carcinoma, 21,22 breast and gastric cancer 23,24 ) and inflammatory disorders (sepsis 25 and acute pancreatitis 26 ) and was identified as a predictor for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic echocardiography was performed as described previously. 16 Blood samples. Blood samples were obtained in the nonfasting state on the second day after admission to the hospital.…”
Section: Assessment Of Patientsmentioning
confidence: 99%
“…Nevertheless, Jiang et al reported that a multiparametric echocardiographic approach has a good diagnostic accuracy in predicting severely augmented sPAP in patients with COPD and PH [33]. PH grading according to invasive and noninvasive measures of pulmonary artery pressures is shown in Table 2 [33,34]. In fact, increased sPAP values can be indirectly estimated by other RV parameters.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…According to some Authors [31,32], in case of increased pulmonary pressure the non-invasive measurement of sPAP is less accurate than the gold-standard method. Nevertheless, Jiang et al reported that a multiparametric echocardiographic approach has a good diagnostic accuracy in predicting severely augmented sPAP in patients with COPD and PH [33]. PH grading according to invasive and noninvasive measures of pulmonary artery pressures is shown in Table 2 [33,34].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…The heart rate and the transcutaneous arterial oxygen saturation were monitored continuously. Transthoracic echocardiography was underdone as described previously [13].…”
Section: Assessment Of Patientsmentioning
confidence: 99%